EFEKTIVITAS CELAH PELOLOSAN (ESCAPE GAP) PADA ALAT TANGKAP PENGILAR UNTUK MENUNJANG KELESTARIAN SUMBERDAYA IKAN - Silka Tria Rezeki; Irwandy Syofyan; Isnaniah ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted during of March until June 2016 in Kampar River and Laboratory of Fishing Gear and Material Faculty of Fisheries and Marine Science University of Riau. The study aim to determine the extent effectivenes of escape gap. The method used are survey and experiment method. The results of this study shown that the circles escape gap can pass the larva of fish with a value of the effectiveness has 0.89Keywords : Pengilar, Escape Gap, Kampar